Hey there guys, how is everyone ? I have another basic boolean question for the gurus out there. I am slowly working my way through my work book and came across this question. prove that A+AB=A using boolean algebra. Now i know that A+AB=A as it a basic rule used to simplify boolean expressions, however actually going through the process is a little difficult for me. When i looked at the answer it showed this: Step 1. A + AB = A Step 2. A(1 + B) = A Step 3. A=A What I was needing help with is I dont know what they have done with step 1 to get to step 2. I see they have factored out the A out of both terms but i dont understand how they have expanded the B term and then canceled it out. If someone could briefly explain to me the steps to go through it would be great !!! Cheers Trev
A logical OR operation indicated by the `+' symbol says 1 .OR. B = 1 which means B can either be a 0 or a 1, we dont care because 1 .OR. 0 = 1 and 1 .OR. 1 = 1 Get it? I knew you would
So, as you said, they factored out the A term. You can see, no matter what state of B, there will be a logic 1 resulting from the 1+B term. So, if B=0, then A(1+0)=A, if B=1, then A(1+1)=A Steve Papabravo beat me by a millisecond!
its simple, in the first step a common was taken which u must have done in your earlier grades in maths (am talking abt factorization). and second step is given correctly by "Scubasteve 911" hope its clear to u